Cybersecurity : a self-teaching introduction - Gupta, C. P.; Goyal, K. K. (Mercury Learning and Information, 2020)
Written in an easy to understand, self-teaching format, this book is designed to provide the reader with the fundamental concepts of cybersecurity and cybercrime. -- Edited summary from book.
Includes index.
Keywords: Computer security.; elektronické knihy; electronic books